Interpersonal Communication Approach in Providing Social Support to Survivors of The Palu City Earthquake - Hajir Muhammad Nur (Jogjakarta Communication Conference (JCC), 2023)
The earthquake that hit Palu City, Central Sulawesi Province on September 28, 2018, resulted in a lot of physical and non-physical losses. The losses that occurred were in the form of damage to infrastructure. The economy and other impacts that also became the concern were traumatic experiences which had an impact on the emergence of post-traumatic stress disorder (Post-traumatic stress), especially in children and adolescents (Syamsuddin, 2019). Post-disaster traumatic experiences like this can have an impact on the most vulnerable group, namely children. Trauma like this cannot be allowed to drag on for a long time because it will have an impact on the child's psychology. Therefore, the aim of this research was to analyze the interpersonal communication approach in the process of social support after the Palu City earthquake. The method employed Play Therapy (play method). This research used a qualitative descriptive research type. Informants in this study were 5 Psychosocial Volunteers who were directly involved after the earthquake and tsunami in Palu City. Data collection techniques used observation and interviews. The results of this study show that social support was provided by psychosocial volunteers using the Play Therapy method in which survivors were invited to play, sing and tell stories. This stage became a way to divert the focus of the survivors' children so they did not remember the disaster they experienced. As a result, the children looked more cheerful and slowly opened up by inviting the volunteers to interact.